Recording ten-fold larger IKr conductances with automated patch clamping using equimolar Cs+ solutions - Bloothooft, Meye; Verbruggen, Bente; Seibertz, Fitzwilliam; Heyden, Marcel A. G. van der; Voigt, Niels; de Boer, Teun P. (Frontiers in Physiology, 2024)
The rapid delayed rectifier potassium current (IKr) is important for cardiac repolarization and is most often involved in drug-induced arrhythmias. However, accurately measuring this current can be challenging in human induced pluripotent stem cells (hiPSC) derived cardiomyocytes, because of its small current density. Interestingly, the ion channel conducting IKr, hERG channel, is not only permeable to K + ions, but also to Cs + ions when present in equimolar concentrations inside and outside of the cell.Methods: In this study IhERG was measured from Chinese Hamster Ovary (CHO)-hERG cells using either Cs + or K + as charge carrier. Equimolar Cs + has been used in literature in manual patch-clamp experiments, here we apply this approach using automated patch-clamp systems. Four different (pre)clinical drugs were tested to compare their effects on Cs + -and K + based currents.Results: Using equimolar Cs + solutions gave rise to approximately ten-fold larger hERG currents.Comparison of Cs + -and K + -mediated currents upon application of dofetilide, desipramine, moxifloxacin or LUF7244, revealed many similarities in inhibition or activation properties of the drugs studied. Using equimolar Cs + solutions gave rise to approximately ten-fold larger hERG currents. In hiPSC-CM the Cs + based current is larger compared to known K + based current and the Cs + hERG current can be inhibited similarly to the K + based current.Using equimolar Cs + instead of K + for IhERG measurements in an automated patch-clamp systems gives rise to a new method by which, for example, quick scans can be performed on effects of drugs on hERG currents. This application is specifically relevant when such experiments are performed using cells which express small IKr current densities in combination with small membrane capacitances.